Semi-polar gallium nitride-based LED based on in-situ SiNx insertion layer
By adopting SiNx insertion layer and 3D to 2D growth method in semi-polar GaN-based LEDs, the challenges of semi-polar GaN-based LEDs in crystal quality, light output efficiency, cost and reliability are solved, and efficient, stable and low-cost LED production is achieved.
Patent Information
- Application Number
- CN202510025233.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-03-07
AI Technical Summary
Existing semi-polar gallium nitride-based LEDs have many challenges in growth technology, light output efficiency, cost, interface characteristics and reliability, limiting their commercial applications.
Using metal organic chemical vapor deposition (MOCVD) technology, by growing SiNx insertion layer in situ and combining the 3D to 2D growth method, the crystal quality of the semi-polar (11-22) GaN template is improved, thread dislocation and other defects are blocked, and compressive stress caused by sapphire substrate is released.
It significantly improves the crystal quality of GaN film, reduces in-plane stress, improves light output efficiency, improves the long-term stability of LEDs, reduces production costs, and expands the application range of LEDs.
Smart Images

Figure CN119584732A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of light emitting diodes, and particularly relates to a method based on in-situ SiN x Semi-polar gallium nitride-based LED with insertion layer and preparation method thereof. Background Art
[0002] In recent years, group III nitrides, represented by gallium nitride, have made significant progress in the field of optoelectronic devices, especially in light-emitting diodes (LEDs). Currently, most commercial gallium nitride-based LEDs are oriented along the c-polar direction. Blue and green LEDs with this polar orientation have achieved great success, but the quantum confined Stark effect (QCSE) generated by this polar orientation leads to band bending and reduced overlap between electron and hole wave functions, resulting in reduced quantum efficiency. In order to circumvent the influence of polar effects, researchers turned their attention to the semi-polar plane and found that devices grown along the semi-polar direction have the advantages of suppressing efficiency drop and spectral shift under high current injection. Among these directions, the chemical potential of the (11-22) semi-polar plane is lower than that of other polar and non-polar surfaces, and can accommodate a higher concentration of indium atoms, making it a viable option for developing LEDs with high indium content (30%) requirements. Typically, (11-22)GaN is grown on (10-10) m-plane sapphire substrates for cost-effectiveness; however, the large lattice mismatch between (11-22)GaN and (10-10) m-plane sapphire produces a high density of extended defects, such as threading dislocations, in (11-22)GaN films, which severely limits the efficiency of GaN-based LEDs.
[0003] Although some progress has been made in the research of semi-polar GaN-based LEDs, there are still some shortcomings: (1) Growth technology challenges: The growth of semi-polar oriented GaN is relatively complex, especially the growth on large-area substrates. It still faces many technical challenges, such as crystal quality and defect density control.
[0004] (2) Light output efficiency: Although the semipolar structure can improve the light output efficiency in some cases, in practical applications, the light output efficiency may not be ideal due to factors such as intrinsic defects and interface roughness.
[0005] (3) Cost: Currently, semi-polar GaN materials and their manufacturing processes are relatively complex, resulting in high production costs, which to a certain extent limits their commercial application.
[0006] (4) Interface characteristics: The interface state of the semi-polar structure may lead to carrier recombination and reduce quantum efficiency.
[0007] (5) Reliability issues: The reliability of semi-polar GaN-based LEDs in long-term operation still needs to be further verified, especially their performance in high power and high temperature environments. Summary of the invention
[0008] In order to solve the above technical problems, the present invention provides a method based on in-situ SiN x The semi-polar GaN-based LED with insertion layer is inserted by in-situ growth of SiN x ) intermediate layer and combined with the 3D to 2D growth method, the crystal quality of the semi-polar (11-22) GaN template is effectively improved. x The insertion layer can block defects such as threading dislocations and improve the crystal quality, while the GaN 3D to 2D process can effectively release the compressive stress on the sapphire substrate. Therefore, long-wavelength LEDs were epitaxially grown based on this high-quality semi-polar (11-22) template.
[0009] In order to solve the above problems, the present invention adopts the following technical solutions: The present invention first discloses a method based on in-situ SiN x The semi-polar GaN-based LED with insertion layer has the following structural features: AlN buffer layer, u-GaN layer, SiN x Insertion layer, u-GaN layer, n-GaN layer, first low In quantum well structure, second low In quantum well structure, third high In quantum well structure, p-GaN layer, p + -GaN layer. Wherein: the first low In quantum well structure and the second low In quantum well structure are both composed of an InGaN layer, a GaN cap layer and an AlGaN barrier layer deposited sequentially from bottom to top; the third high In quantum well structure is composed of an InGaN layer, an AlGaN cap layer and an AlGaN barrier layer deposited sequentially from bottom to top.
[0010] Preferably, the sapphire substrate is a sapphire substrate with a (10-10) m-plane orientation.
[0011] Preferably, the u-GaN layer, the n-GaN layer, the p-GaN layer, the p + -GaN layer and each layer in the quantum well structure are semi-polar (11-22) orientation.
[0012] Preferably, the SiN x The insertion layer has a nanoscale hole structure, which provides an in-situ mask template for the subsequent u-GaN growth, allowing u-GaN to start three-dimensional growth from the nanoscale holes to form a 3D island structure, and then continue to grow in 2D in the horizontal and vertical directions to form a flat and smooth u-GaN layer.x The insertion layer can isolate some dislocations and defects and improve the crystal quality of semi-polar u-GaN. Due to the lattice mismatch between the sapphire substrate and u-GaN, it will be subjected to the compressive stress of the sapphire substrate. The above-mentioned 3D to 2D growth method can effectively release the compressive stress. Therefore, the u-GaN grown by the present invention is a stress-relaxed, high-quality semi-polar (11-22) GaN template.
[0013] The present invention further provides a method for preparing the semi-polar gallium nitride-based LED based on the in-situ SiNx insertion layer, which is to use TMGa or TEGa, TMAl, TMIn and NH3 as the sources of gallium, aluminum, indium and nitrogen respectively in a MOCVD system, use SiH4 as the silicon source and the n-type doping source of the n-GaN layer, and use CP2Mg as the p-GaN layer and the p-GaN layer. + -GaN layer p-type doping source, using nitrogen, hydrogen or a mixture of nitrogen and hydrogen as carrier gas, is deposited layer by layer, including the following steps: Step 1: Pre-treat the substrate Commonly used substrate materials include silicon (Si), silicon carbide (SiC) and sapphire (Al2O3). Silicon substrates are widely used in the semiconductor industry, but epitaxial gallium nitride on silicon substrates has a large number of mismatch dislocations. Compared with gallium nitride, silicon carbide substrates have relatively small thermal mismatch and lattice mismatch, and are ideal materials for epitaxial gallium nitride-based LEDs. However, the processing and treatment of silicon carbide substrates are very difficult and the price is very expensive, making them unsuitable for large-scale commercial use. Sapphire substrates are cheap and easy to obtain, transparent and light-proof, and have a small lattice mismatch, so sapphire substrates are the most suitable.
[0014] The sapphire substrate is heated at 1000-1200°C for 10-15 minutes in a mixed atmosphere of NH3 and N2. This operation can inhibit the formation of the subsequent (10-13) mixed phase of the GaN film to obtain a pure (11-22) oriented GaN film.
[0015] Step 2: Deposit AlN buffer layer A 15-18 nm thick AlN buffer layer was grown on a sapphire substrate at a temperature of 1050-1150°C and a pressure of 50-100 Torr.
[0016] Step 3: Deposit u-GaN layer A 1.5-2 μm thick u-GaN layer is grown on an AlN buffer layer at a temperature of 1000-1100°C, a pressure of 100-200 Torr, and a V / III ratio of 1000-1100. The V / III ratio is also called the input V / III ratio, which refers to the molar ratio of the V group source to the III group source introduced into the reaction chamber.
[0017] Step 4: Growth of SiN x Insertion layer At a temperature of 900-1000°C and a pressure of 100-200 Torr, SiN is in-situ deposited on the u-GaN layer obtained in step 3. x Insertion layer, deposition time is 5~7 minutes.
[0018] Step 5: Growth of u-GaN layer First, a 3D island structure is grown at a temperature of 900-950°C, a pressure of 100-200 Torr, and a V / III ratio of 30-50 for 1-5 min. Then, the temperature is adjusted to 1050-1100°C, the pressure is 100-200 Torr, and the V / III ratio is 1000-1100, and 2D growth is continued in the lateral and longitudinal directions until the SiN x A u-GaN layer with a thickness of 1.5~2 µm is formed on the insertion layer.
[0019] Step 6: Grow n-GaN layer At a temperature of 1050-1100°C and a pressure of 100-200 Torr, a 2-3µm thick Si-doped n-GaN layer is grown on the u-GaN layer obtained in step 5, and the Si doping concentration is 2-5×10 19 cm −3 .
[0020] Step 7: Growing quantum well structure The growth conditions of the first low In quantum well structure and the second low In quantum well structure are: The thickness of the InGaN layer is 3~3.5 nm, and its atomic percentage composition is In 0.18 Ga 0.82 N, growth temperature is 765~785℃, pressure is 200~250 Torr; The thickness of the GaN cap layer is 1-2 nm, the growth temperature is 765-785°C, and the pressure is 200-250 Torr; The thickness of the AlGaN barrier layer is 10~20 nm, and its atomic percentage composition is Al 0.05 Ga 0.95 N, growth temperature is 765~785℃, pressure is 200~250 Torr; The growth conditions of the third highest In quantum well structure are: The thickness of the InGaN layer is 3~3.5 nm, and its atomic percentage composition is In 0.3 Ga 0.7 N, growth temperature is 725~735℃, pressure is 400~450 Torr; The thickness of the AlGaN cap layer is 1~2nm, and its composition in atomic percentage is Al 0.2 Ga 0.8 N, growth temperature is 725~735℃, pressure is 400~450Torr; The thickness of the AlGaN barrier layer is 20~30nm, and its composition in atomic percentage is Al 0.05 Ga 0.95 N, growth temperature is 725~735℃, pressure is 400~450Torr; Step 8: Growth of p-GaN layer At a temperature of 950-1000°C and a pressure of 100-200 Torr, a 100-150 nm thick Mg-doped p-GaN layer is grown on the quantum well structure obtained in step 7, and the Mg doping concentration is 2-5×10 19 cm −3 ; Step 9: Growth p + -GaN At a temperature of 885-900°C and a pressure of 100-200 Torr, a 50-60 nm thick Mg heavily doped p-GaN layer was grown on the p-GaN layer obtained in step 8. + -GaN layer, Mg doping concentration is 2~5×10 20 cm −3 , that is, to obtain in-situ SiN x Semi-polar GaN-based LED with insertion layer.
[0021] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. Improve crystal quality: The present invention uses SiN x As an insertion layer of the u-GaN layer, it can effectively block the propagation of threading dislocations and other extended defects, thereby significantly improving the crystal quality of GaN thin films. This improvement is crucial to optimizing the optoelectronic performance of LED devices and can improve the quantum efficiency and luminescence performance of the device.
[0022] 2. Reducing in-plane stress: The present invention utilizes SiN x The nanoscale hole structure of the insertion layer is used as a mask to grow u-GaN through 3D to 2D conversion, which can effectively release the compressive stress of u-GaN on the sapphire substrate, which helps to reduce the formation of internal defects in the material and thus improve the light output and long-term stability of the LED.
[0023] 3. Improve light output efficiency: Semi-polar LEDs grown on high-quality GaN substrates can effectively suppress efficiency drop and spectrum shift under high current injection, thereby improving light output efficiency under high power operation. This makes semi-polar LEDs more competitive in applications.
[0024] 4. Wide wavelength adjustment capability: Since the chemical potential of the (11-22) semi-polar plane is lower than that of other polar and non-polar surfaces, it can accommodate a higher concentration of indium atoms, which provides a good platform for the development of long-wavelength LEDs with high indium content and expands the application range of LEDs.
[0025] 5. Optimize quantum efficiency: Semi-polar GaN suppresses the quantum confined Stark effect (QCSE), which improves wave function overlap and helps improve the quantum efficiency of the device, which is especially important in the design of long-wavelength LEDs.
[0026] 6. Improve compatibility: Utilize existing sapphire substrates and combine with SiN x The use of insertion layers facilitates compatibility with existing LED manufacturing processes and reduces equipment investment and R&D costs required to introduce new materials.
[0027] 7. Strong scalability: The method of the present invention has good scalability for large-area growth of semi-polar GaN-based LEDs, provides a possible solution for large-scale manufacturing of long-wavelength LEDs, and is easier to realize commercial applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 In Example 1, based on in-situ SiN x Schematic diagram of the structure of each layer of the semi-polar GaN-based LED with an insertion layer; Figure 2 In Example 1, based on in-situ SiN x Schematic diagram of the preparation process of semi-polar GaN-based LED with insertion layer; Figure 3 Scanning electron microscope (SEM) images of the GaN 3D islands at the initial stage of formation and after 5 minutes of growth in Example 1; Figure 4 In Example 1, SiN x Schematic diagram of the transition from 3D growth to 2D growth of the GaN layer on the insertion layer; Figure 5 Schematic diagram of the strain modulation mechanism related to the agglomeration of GaN grains when the 3D growth is transformed into the 2D growth in Example 1; Figure 6 In Example 1, based on in-situ SiN x AFM image of a semi-polar GaN-based LED with an insertion layer; Figure 7 The difference between Example 1 and Comparative Example 1 is shown in Table 1. x XRD comparison of u-GaN grown by insertion layer; Figure 8 For Example 1 ( Figure 8(a)) and Comparative Example 1 ( Figure 8 In (b)), there is SiN or not x Raman contrast image of u-GaN grown by insertion layer; Fig. 9 The in-situ SiN prepared in Example 1 x Insertion layer semi-polar GaN-based LEDs at 1 to 10 A / cm 2 Electroluminescence spectra of the semi-polar LED at different current densities. The inset shows the electroluminescence spectra of the semi-polar LED at a current density of 1 A / cm 2 Luminescence image under an optical microscope; Fig.10 The SiN-free prepared in Comparative Example 1 x Insertion layer semi-polar GaN-based LEDs at 1 to 10 A / cm 2 Electroluminescence spectra of the semi-polar LED at different current densities. The inset shows the electroluminescence spectra of the semi-polar LED at a current density of 1 A / cm 2 Luminescence image under an optical microscope; Fig.11 The difference between Example 1 and Comparative Example 1 is shown in Table 1. x Comparison of peak wavelengths of LEDs with inserted layers. DETAILED DESCRIPTION
[0029] The embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. The following embodiments are implemented based on the technical solutions of the present invention, and provide detailed implementation methods and specific operation processes.
[0030] Example 1 like Figure 1 As shown, this embodiment provides a method based on in-situ SiN x The semi-polar GaN-based LED with insertion layer is deposited on the sapphire substrate from bottom to top: AlN buffer layer, u-GaN layer, SiN x Insertion layer, u-GaN layer, n-GaN layer, first low In quantum well structure, second low In quantum well structure, third high In quantum well structure, p-GaN layer, p + -GaN layer. Among them: the first low In quantum well structure and the second low In quantum well structure are both composed of an InGaN layer, a GaN cap layer and an AlGaN barrier layer deposited sequentially from bottom to top; the third high In quantum well structure is composed of an InGaN layer, an AlGaN cap layer and an AlGaN barrier layer deposited sequentially from bottom to top.
[0031] like Figure 2 As shown, this embodiment also provides an in-situ SiN xThe preparation method of the semi-polar gallium nitride-based LED with an insertion layer is completed in the MOCVD system throughout the preparation process, using TMGa, TMAl, TMIn and NH3 as the sources of gallium, aluminum, indium and nitrogen respectively, SiH4 as the silicon source and n-type doping source, CP2Mg as the p-type doping source, and nitrogen as the carrier gas for layer-by-layer deposition. The specific steps are as follows: Step 1: Pre-treat the substrate First, a 2-inch (10-10) m-plane sapphire substrate was treated in a mixed gas of NH3 and N2 (flow ratio 1:1) at 1100°C for 10 min.
[0032] Step 2: Deposit AlN buffer layer A 15 nm thick AlN buffer layer was grown on a sapphire substrate at a temperature of 1100°C, a pressure of 65 Torr, and a V / III ratio of 1000.
[0033] Step 3: Deposit u-GaN layer Under the conditions of temperature 1050°C, gas pressure 100 Torr, and V / III ratio of 1000, a 1.5 μm thick u-GaN layer was grown on the AlN buffer layer.
[0034] Step 4: Growth of SiN x Insertion layer At a temperature of 900°C and a pressure of 100 Torr, SiN was in-situ deposited on the u-GaN layer obtained in step 3. x Insert layer, deposition time is 7 minutes.
[0035] Step 5: Grow high-quality u-GaN layer First, a 3D island structure was grown at 950°C, 100 Torr, and 30 V / III ratios for 1 min. Then, the temperature was adjusted to 1050°C, 100 Torr, and 1000 V / III ratios to continue 2D growth in the lateral and longitudinal directions until the SiN x A u-GaN layer with a thickness of 1.5 μm was formed on the insertion layer.
[0036] Step 6: Grow n-GaN layer At a temperature of 1075°C, a pressure of 100 Torr, and a V / III ratio of 1000, a 2 µm thick Si-doped n-GaN layer was grown on the u-GaN layer obtained in step 5. The Si doping concentration was 2×10 19 cm −3 .
[0037] Step 7: Growing quantum well structure The growth conditions of the first low In quantum well structure and the second low In quantum well structure are: The thickness of the InGaN layer is 3 nm, and its atomic percentage composition is In 0.18 Ga 0.82 N, growth temperature 785 ° C, gas pressure 200 Torr, V / III ratio 1000; The thickness of the GaN cap layer is 1 nm, the growth temperature is 785°C, the pressure is 200 Torr, and the V / III ratio is 1000; The thickness of the AlGaN barrier layer is 10 nm, and its atomic percentage composition is Al 0.05 Ga 0.95 N, growth temperature 785 ° C, gas pressure 200 Torr, V / III ratio 1000; The growth conditions of the third highest In quantum well structure are: The thickness of the InGaN layer is 3.5 nm, and its atomic percentage composition is In 0.3 Ga 0.7 N, growth temperature 735 °C, gas pressure 400 Torr, V / III ratio 1000; The thickness of the AlGaN cap layer is 1 nm, and its atomic percentage composition is Al 0.2 Ga 0.8 N, growth temperature 735 °C, gas pressure 400 Torr, V / III ratio 1000; The thickness of the AlGaN barrier layer is 30 nm, and its atomic percentage composition is Al 0.05 Ga 0.95 N, growth temperature is 735℃, gas pressure is 400 Torr, and V / III ratio is 1000.
[0038] Step 8: Growth of p-GaN layer At a temperature of 960°C, a pressure of 100 Torr, and a V / III ratio of 1000, a 100 nm thick Mg-doped p-GaN layer was grown on the quantum well structure obtained in step 7. The Mg doping concentration was 2×10 19 cm −3 .
[0039] Step 9: Growth p + -GaN At a temperature of 885°C, a pressure of 100 Torr, and a V / III ratio of 1200, a 50 nm thick Mg heavily doped p-GaN layer was grown on the p-GaN layer obtained in step 8. + -GaN layer, Mg doping concentration is 2×10 20 cm −3 , that is, to obtain the in-situ SiN x Semi-polar GaN-based LED with insertion layer.
[0040] Figure 3 The scanning electron microscope (SEM) images of the GaN 3D islands in step 5 at the initial stage (about 1 minute) and after 5 minutes of growth. The GaN islands are first formed on the SiN x They nucleate in the pores of the layer and then grow along the [-1-123] and [1-100] directions, gradually forming a three-dimensional island structure, which will then merge horizontally and vertically.
[0041] Figure 4 For SiN x Schematic diagram of the GaN layer grown on the insertion layer. SiN x The insertion layer contains nanoscale pores. Under extremely low V / III conditions, GaN is deposited in porous SiN x Subsequently, the 3D GaN islands undergo 2D growth both laterally and vertically until they are x A u-GaN layer with a thickness of 1.5 μm is formed over the insertion layer.
[0042] Figure 5 Schematic diagram of the strain modulation mechanism related to grain agglomeration when GaN grows from 3D to 2D. In the early stage of GaN layer growth in step 5, these three-dimensional GaN islands merge with each other, which is called grain agglomeration. Adjacent islands are pulled together to form grain boundaries, which leads to the expansion of the GaN surface lattice, and the GaN is subjected to compressive stress and becomes tensile stress, becoming a stress-relaxed semipolar (11-22) GaN template.
[0043] Figure 6 The in-situ SiN x Atomic force microscopy (AFM) image of the surface of a semi-polar GaN-based LED with an insertion layer, with a root mean square roughness value (RMS) of 12.6 nm. The surface of the sample exhibits an "arrow" structure or wedge shape, which is caused by the anisotropic surface diffusion lengths along the [1-100] and [-1-123] directions.
[0044] Comparative Example 1 To verify SiN x The effect of the insertion layer on the LED performance. x The semi-polar GaN-based LED with an insertion layer has a device structure that is different from the device structure in Example 1 except that there is no SiN x Insertion layer. The preparation method thereof is different from that in Example 1, except that step 4 is not performed.
[0045] Figure 7 The difference between Example 1 and Comparative Example 1 is shown in Table 1. xXRD comparison of u-GaN grown by inserting layer. x The insertion layer can improve the quality of the semi-polar (11-22) GaN template and reduce the anisotropy.
[0046] Figure 8 The difference between Example 1 and Comparative Example 1 is shown in Table 1. x Raman contrast of u-GaN grown by insertion layer. In the case of semi-polar GaN, the E2(high) peak of unstressed GaN is located at 568 cm -1 , no SiN x The u-GaN grown by the insertion layer has a red shift of 2.67 cm -1 , while the red shift of u-GaN grown with SiNx insertion layer is 1.69 cm -1 . No SiN x The calculated stress of u-GaN grown as the insertion layer is 0.43 GPa. x The calculated stress of u-GaN grown by the insertion layer is 0.27 GPa, which shows that there is no SiN x The u-GaN grown in the insertion layer is subject to less compressive stress.
[0047] Fig. 9 The in-situ SiN prepared in Example 1 x Insertion layer semi-polar GaN-based LEDs at 1 to 10 A / cm 2 Electroluminescence spectra of the LED at different current densities. It can be seen from the figure that the LED does not have any parasitic blue emission. The inset in the figure shows the semi-polar LED at a current density of 1 A / cm 2 When the luminescence image is taken under an optical microscope, the LED emits pure red light.
[0048] Fig.10 The SiN-free prepared in Comparative Example 1 x Insertion layer semi-polar GaN-based LEDs at 1 to 10 A / cm 2 The electroluminescence spectra of the LED at different current densities show that the LED does not have any parasitic blue emission. However, the luminescence image in the inset shows that the LED emits orange-yellow light.
[0049] Fig.11 The difference between Example 1 and Comparative Example 1 is shown in Table 1. x The peak wavelength comparison of the LED of the insertion layer. It can be seen from the figure that when the current density is 1 A / cm 2 When SiN x The peak wavelength of the LED with inserted layer is higher than that without SiN xThe peak wavelength of the LED with the inserted layer is 24.4 nm higher. When the injection current density increases from 1 A / cm² to 100 A / cm², the SiN-free x Insert layer LED and SiN x The blue shifts of the LEDs with the inserted layer are 36.7 nm and 33.1 nm respectively. x The wavelength of the LED in the insertion layer is longer and its blue shift is smaller.
[0050] The above description is only an exemplary embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. Based on in-situ SiN x Insertion layer semi-polar GaN-based LED, characterized in that, The following layers are deposited on the sapphire substrate from bottom to top: AlN buffer layer, u-GaN layer, SiN x Insertion layer, u-GaN layer, n-GaN layer, first low In quantum well structure, second low In quantum well structure, third high In quantum well structure, p-GaN layer, p + -GaN layer; The first low In quantum well structure and the second low In quantum well structure are both composed of an InGaN layer, a GaN cap layer and an AlGaN barrier layer deposited sequentially from bottom to top; the third high In quantum well structure is composed of an InGaN layer, an AlGaN cap layer and an AlGaN barrier layer deposited sequentially from bottom to top.
2. The in-situ SiN-based method according to claim 1 x Insertion layer semi-polar GaN-based LED, characterized in that, The sapphire substrate has a (10-10) m-plane orientation.
3. The in-situ SiN-based method according to claim 1 or 2. x A semi-polar GaN-based LED with an insertion layer, characterized in that: u-GaN layer, n-GaN layer, p-GaN layer, p + -GaN layer and each layer in the quantum well structure are semi-polar (11-22) orientation.
4. The in-situ SiN-based method according to claim 1 or 2 x A semi-polar GaN-based LED with an insertion layer, characterized in that: The SiN x The insertion layer has a nanoscale hole structure, which provides an in-situ mask template for the subsequent growth of u-GaN, allowing u-GaN to start three-dimensional growth from the nanoscale holes to form a 3D island structure, and then continue with 2D growth in the lateral and vertical directions to form a u-GaN layer.
5. An in-situ SiN-based method according to any one of claims 1 to 4 x A method for preparing a semi-polar gallium nitride-based LED with an insertion layer, characterized in that: In the MOCVD system, TMGa or TEGa, TMAl, TMIn and NH3 are used as the sources of gallium, aluminum, indium and nitrogen respectively, SiH4 is used as the silicon source and n-type doping source, CP2Mg is used as the p-type doping source, and nitrogen, hydrogen or a mixture of nitrogen and hydrogen is used as the carrier gas to perform layer-by-layer deposition, including the following steps: Step 1: Pre-treat the substrate Heat the sapphire substrate in a mixed atmosphere of NH3 and N2 at 1000-1200°C for 10-15 minutes; Step 2: Deposit AlN buffer layer A 15-18 nm thick AlN buffer layer was grown on a sapphire substrate at a temperature of 1050-1150°C and a pressure of 50-100 Torr. Step 3: Deposit u-GaN layer Under the conditions of temperature 1000~1100℃, gas pressure 100~200 Torr, and V / III ratio 1000~1100, a 1.5~2 μm thick u-GaN layer is grown on the AlN buffer layer; Step 4: Growth of SiN x Insertion layer At a temperature of 900-1000°C and a pressure of 100-200 Torr, SiN is in-situ deposited on the u-GaN layer obtained in step 3. x Insertion layer, deposition time is 5-7 minutes; Step 5: Growth of u-GaN layer First, a 3D island structure is grown at a temperature of 900-950°C, a pressure of 100-200 Torr, and a V / III ratio of 30-50 for 1-5 min. Then, the temperature is adjusted to 1050-1100°C, the pressure is 100-200 Torr, and the V / III ratio is 1000-1100, and 2D growth is continued in the lateral and longitudinal directions until the SiN x A u-GaN layer with a thickness of 1.5 to 2 µm is formed on the insertion layer; Step 6: Grow n-GaN layer At a temperature of 1050-1100°C and a pressure of 100-200 Torr, a 2-3 µm thick Si-doped n-GaN layer is grown on the u-GaN layer obtained in step 5, and the Si doping concentration is 2-5×10 19 cm −3 ; Step 7: Growing quantum well structure The growth conditions of the first low In quantum well structure and the second low In quantum well structure are: The thickness of the InGaN layer is 3~3.5 nm, and its atomic percentage composition is In 0.18 Ga 0.82 N, growth temperature is 765~785℃, pressure is 200~250 Torr; The thickness of the GaN cap layer is 1-2 nm, the growth temperature is 765-785°C, and the pressure is 200-250 Torr; The thickness of the AlGaN barrier layer is 10~20 nm, and its atomic percentage composition is Al 0.05 Ga 0.95 N, growth temperature is 765~785℃, pressure is 200~250 Torr; The growth conditions of the third highest In quantum well structure are: The thickness of the InGaN layer is 3~3.5 nm, and its atomic percentage composition is In 0.3 Ga 0.7 N, growth temperature is 725~735℃, pressure is 400~450 Torr; The thickness of the AlGaN cap layer is 1~2 nm, and its atomic percentage composition is Al 0.2 Ga 0.8 N, growth temperature is 725~735℃, pressure is 400~450 Torr; The thickness of the AlGaN barrier layer is 20~30 nm, and its atomic percentage composition is Al 0.05 Ga 0.95 N, growth temperature is 725~735℃, pressure is 400~450 Torr; Step 8: Growth of p-GaN layer At a temperature of 950-1000°C and a pressure of 100-200 Torr, a 100-150 nm thick Mg-doped p-GaN layer is grown on the quantum well structure obtained in step 7, and the Mg doping concentration is 2-5×10 19 cm −3 ; Step 9: Growth p + -GaN At a temperature of 885-900°C and a pressure of 100-200 Torr, a 50-60 nm thick Mg heavily doped p-GaN layer was grown on the p-GaN layer obtained in step 8. + -GaN layer, Mg doping concentration is 2~5×10 20 cm −3 , that is, to obtain in-situ SiN x Semi-polar GaN-based LED with insertion layer.
Citation Information
Patent Citations
LED epitaxial wafer and production method thereof
CN103456852A
Group iii nitride semiconductor light-emitting device
CN103682001A
Preparation method of semi-polar m-plane GaN base semiconductor device containing SiNx insertion layer
CN103952683A
Epitaxial growth method of silicon substrate GaN-based LED
CN108110093A
Semi-polarity gallium nitride epitaxial layer structure and preparation method
CN109449269A